La sociedad civil y el primer peronismo. El fomentismo de Bahía Blanca y su lugar dentro de la “comunidad organizada” - José Marcilese (Nuevo mundo - Mundos Nuevos, 2009)
The relationship Peronism established with the organizations of civil society is a historical aspect partially unexplored so far. This paper aims at addressing the relationship established between the neighbors' associations in Bahía Blanca and the Peronist government, especially when it began a gradual process of “peronisation” of civil society associations which affected the dynamics of neighbors' associations. In the case of Bahía Blanca, this process was also influenced by the creation of the unidades básicas (Peronist Party committees) which competed from an early stage with the neighbors' associations to represent the interests and concerns of neighbors.